Thermo-economical and environmental analyses of a Direct Contact Membrane Distillation (DCMD) performance. (15th March 2022) - Okati, Vahab; Moghadam, Ali Jabari; Farzaneh-Gord, Mahmood; Moein-Jahromi, Mahbod
Abstract: As a promising desalination technology, membrane distillation is expected to be developed continuously due to its wide application and low sensitivity to salt concentration in the feed stream. The performance of a direct contact membrane distillation (DCMD) has been investigated based on energy, exergy, economic and environmental analyses in the current study. Performance evaluation of a DCMD unit is comprehensively carried out in terms of the operating parameters, including gained output ratio (GOR), specific energy consumption (SEC), concentration polarization coefficient, temperature polarization coefficient, recovery ratio, exergy efficiency, specific exergy consumption, carbon cost, and cost of water. This study presents one of the most comprehensive investigations on DCMD behavior performed in the available literature by developing a robust computational code in MATLAB software. In addition to pervasive energy and exergy analyses, a complete economic study for freshwater production plants with different capacities based on heat extracted through geothermal energy and wasted heat, and investigation of the environmental effects of using heat recovery MD cycle to reduce greenhouse gas emissions, are presented. The results showed that the utilization of heat recovery heat exchangers significantly improves the system's operating conditions. The exergy efficiency of the DCMD module with and without heat recovery is 38.23% and 56.71%, respectively, indicating a 48.34% improvement in exergy efficiency. Finally, the economic and environmental analyses showed that for a 15000 m 3 /day desalination unit, recovering the wasted heat could reduce the distillate water production cost down to 1.31 $/m 3 while C O 2 emissions and energy consumption also decreased by 59%. Graphical abstract: Image 1